Experience with Ontario's Parenting Plan Guide and Template. (1st August 2022) - Birnbaum, Rachel; Bala, Nicholas
Abstract: Detailed, voluntary parenting plans are being increasing used in many jurisdictions. In conjunction with legislative reforms that came into effect in Canada in 2021 and specifically provide for parenting plans in place of traditional custody and access orders, the Ontario Chapter of the Association of Family and Conciliation Courts (AFCC-O) tasked a multidisciplinary group to prepare materials to assist professionals and parents in making parenting plans, including providing developmentally appropriate advice about parenting time schedules. This research project involved surveys and interviews with a total of 103 participants (lawyers, judges, mediators, mental health professionals, and parents) about their experiences with parenting plans and the AFCC-O materials. The use of parenting plans has increased as a result of the legislative changes, new resources to assist in making plans, and the accompanying professional education programmes. Professionals and parents appreciate having access to the type of jurisdictionally specific resource materials prepared by multidisciplinary groups, and judges have made significant use of these materials. The materials are especially useful for parents who have access to appropriate professional support and who have good literacy skills, and for lower conflict cases. It is, however, clear that the parenting plan materials have limitations, and in particular these resources have limited utility for self-represented litigants and cannot help in resolving higher conflict cases and those cases where family violence exists.